2010
DOI: 10.1002/er.1743
|View full text |Cite
|
Sign up to set email alerts
|

Constructal design of distributed cooling on the landscape

Abstract: SUMMARYHere we constructal design to determine the area size (or number of users N) to be allocated to a central refrigeration plant, and to configure the distribution network for the distributed cooling system. The main objective is to maximize the net cooling capacity delivered to every user, and to minimize the pumping power required for transporting the chilled water. Two types of distribution networks are investigated: radial and tree-shaped networks. First, when ducts with a single diameter are used, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…He introduced the global objective as the maximum possible amount of liquid distilled, and the global constraint as the total size of the reflective plate and cover. Xia et al [19] found the optimal area size that should be allocated 1 to a central refrigeration plant. Then, the best configuration of distribution network for the distributed cooling system was determined.…”
Section: Introductionmentioning
confidence: 99%
“…He introduced the global objective as the maximum possible amount of liquid distilled, and the global constraint as the total size of the reflective plate and cover. Xia et al [19] found the optimal area size that should be allocated 1 to a central refrigeration plant. Then, the best configuration of distribution network for the distributed cooling system was determined.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach is inspired by Constructal design which demonstrates how the optimal distribution of products and services flows across a populated area depends on a balance between the size of the production centers and the sizes of distribution networks that connect these centers to end users . Although larger systems are thermodynamically more efficient in production, they serve larger areas; thus, the collection and distribution logistical costs also increase with size, as do potential environmental impacts and public opposition .…”
Section: Methodsmentioning
confidence: 99%
“…This balance has been used for analyzing both the thermodynamics of energy sources and the economics of agricultural/biofuel systems . Applications of the balance principle have been demonstrated for various systems such as the thermodynamic optimization of hot water flow and heating, refrigeration, combined solar power and desalination, and agricultural product processing economics . The balance principle has also led to proposals for distributed energy systems to optimize energy production size and service area .…”
Section: Methodsmentioning
confidence: 99%
“…The configuration with parallel channels had N channels of diameter D f and height H. The diameter D f was chosen from Eq. (17), which means that a given porosity and total volume of the configuration is known from the solid thickness to the number of channels N. The corresponding overall pressure losses were expressed in Eq. (22),…”
Section: Trees Alternating With Upside Down Treesmentioning
confidence: 99%
“…In this paper, we rely on the constructal law in order to propose a novel perspective on how to design a regenerator. According to the constructal law, all flow systems (animate and inanimate) have the natural tendency to evolve their configurations (their designs) in time so that they flow more easily [14][15][16][17][18][19][20][21][22][23]. In the regenerator design perspective that we construct, flowing more easily means an evolutionary design (a morphing architecture) toward flowing with lower and better distributed thermal and fluid resistances such that the 'whole' exhibits a greater performance.…”
Section: Introductionmentioning
confidence: 99%